Comparative Effects of Repetitive Transcranial Magnetic Stimulation and Theta-Burst Stimulation on Post-Stroke Dysphagia: A Systematic Review and Meta-Analysis of Randomized Controlled Trials. - Liu, Chunhua; Wang, Jiayan; Lin, Huajian; Ye, Zegen; Wang, Liqin; Liu, Xilin; Zheng, Yongfei (NeuroRehabilitation, 2025)
Objectives: To systematically review the effects of transcranial magnetic stimulation (TMS) on post-stroke dysphagia, focusing on stimulation mode, frequency, and target region. Methods: This systematic review followed PRISMA guidelines and was registered in PROSPERO (CRD42025631286). We systematically searched PubMed, Cochrane Central, and Embase for RCTs on TMS for post-stroke dysphagia up to December 11, 2024. Meta-analysis was conducted using Stata 16, with heterogeneity assessed via the I2 statistic. Subgroup and sensitivity analyses explored sources of heterogeneity. Risk of bias and study quality were evaluated using the Cochrane Risk of Bias 2.0 (RoB 2) tool and the Physiotherapy Evidence Database (PEDro) scale. Results: This meta-analysis included 14 RCTs with 882 stroke patients, assessing swallowing function using the Penetration-Aspiration Scale (PAS), Standardized Swallowing Assessment (SSA), Functional Dysphagia Scale (FDS), Fiberoptic Endoscopic Dysphagia Severity Scale (FEDSS), and Functional Oral Intake Scale (FOIS). The results showed that TMS significantly improved swallowing function across all scales: PAS (MD = −1.32, 95% CI: −1.50 to −1.14, P < 0.001), SSA (MD = −1.97, 95% CI: −2.43 to −1.50, P < 0.001), FEDSS (MD = −0.65, 95% CI: −0.84 to −0.46, P < 0.001), FOIS (MD = 0.92, 95% CI: 0.72 to 1.13, P < 0.001), and FDS (MD = −5.54, 95% CI: −7.48 to −3.60, P < 0.001). Conclusion: This meta-analysis demonstrates that TMS significantly improves swallowing function in stroke patients, with consistent effects across scales, interventions, stimulation modes, and targets. However, variability in protocols and short follow-up periods may limit the generalizability of the findings.